DEVELOPPEMENT FINANCIER ET CROISSANCE ECONOMIQUE DANS LES PAYS AFRICAINS DE LA ZONE FRANC : LE ROLE DE LA GOUVERNANCE - Kuipou Toukam Christophe; Nembot Ndeffo Luc; Tafah Edokat O. Edward (European Scientific Journal, ESJ, 2015)
This paper studies the effect of Financial development on economic growth through the institutions. The results obtained using Generalized Moments Method (GMM) in the dynamic panel show that the direct effect of governance on growth in the franc zone is not significant. Comparing the results of the two sub regions, it is positive but insignificant in EMCCA while it is positive and significant in the WAEMU zone. In addition, financial development (CPRIV and LIQ) negatively affects economic growth in EMCCA and WAEMU while credit from the banking sector has a positive effect in some cases.The results of the indirect effect show that the combined effect Governance-Financial development remains negative and insignificant in EMCCA while in the WAEMU zone , this effect is negative and insignificant except GOUV.CBANC whose effect is negative and significant. However, it is positive but insignificant in the Franc zone. Thus, the institutional framework does not contribute to the improvement of the effect of financial development on economic growth in EMCCA and WAEMU . This result is also verified in 0 % of cases in the EMCCA zone while it was 100% in the WAEMU zone and Frank respectively . These results allowed us to calculate a threshold beyond which the institutional framework enhances the effect of financial development on economic growth, which is respectively 0.09 , 0.09 and 1.77 in Zone Franc , EMCCA and WAEMU financial variables LIQ , and CBANC LIQ . We recommend these countries to try to improve their institutional framework by making favorable conditions for the fight against corruption , bureaucracy and a greater political stability which will contribute to the development of their financial systems. Similarly , institutional liberalization should precede financial liberalization.